2017
DOI: 10.1002/14651858.cd006109.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive pill, progestogen or oestrogen pretreatment for ovarian stimulation protocols for women undergoing assisted reproductive techniques

Abstract: Oral contraceptive pill, progestogen or oestrogen pretreatment for ovarian stimulation protocols for women undergoing assisted reproductive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 130 publications
2
33
0
1
Order By: Relevance
“…It is believed that OC act to suppress endogenous gonadotropin secretion thus preventing spontaneous LH-surge and assist in the synchronization of follicular development when given prior to gonadotropin stimulation, leading to a higher egg yield and increased chances of pregnancy ( Kim et al, 2009 ). However, the results of our study demonstrate lower LBR following fresh embryo transfer in patients using the GnRH-ant protocol for ovarian stimulation, which is consistent with previously published studies ( Garcia-Velasco and Fatemi, 2015 ; Farquhar et al, 2017 ; Wei et al, 2017 ; Xu et al, 2019b ). Results of a recent meta-analysis of 6 RCTs by Farquhar et al reported that OC pretreatment was associated with a lower ongoing pregnancy rate/LBR after a fresh embryo transfer (OR 0.74, 95% CI: 0.58–0.95) in GnRH-ant cycles ( Farquhar et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is believed that OC act to suppress endogenous gonadotropin secretion thus preventing spontaneous LH-surge and assist in the synchronization of follicular development when given prior to gonadotropin stimulation, leading to a higher egg yield and increased chances of pregnancy ( Kim et al, 2009 ). However, the results of our study demonstrate lower LBR following fresh embryo transfer in patients using the GnRH-ant protocol for ovarian stimulation, which is consistent with previously published studies ( Garcia-Velasco and Fatemi, 2015 ; Farquhar et al, 2017 ; Wei et al, 2017 ; Xu et al, 2019b ). Results of a recent meta-analysis of 6 RCTs by Farquhar et al reported that OC pretreatment was associated with a lower ongoing pregnancy rate/LBR after a fresh embryo transfer (OR 0.74, 95% CI: 0.58–0.95) in GnRH-ant cycles ( Farquhar et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Oral contraceptives (OC) have been widely used to prevent pregnancy, and for the treatment of dysmenorrhea or menstrual disorders since being first approved in 1960 ( Golobof and Kiley, 2016 ). With the increasing utilization of in vitro fertilization-embryo transfer (IVF-ET) world-wide, OC have extensively been employed as a pretreatment before controlled ovarian stimulation in IVF cycles ( Farquhar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one article was removed over duplication. Further 18 articles were excluded (Bjelakovic et al, 2012;Chen & Lina, 2016;Consales et al, 2014;Farquhar et al, 2017;Garolla et al, 2014;Hart et al, 2015;Li et al, 2016;MacArthur et al, 2014;Nicoletti et al, 2016;Nisenblat et al, 2016;Pourmand et al, 2014;Povey et al, 2012;Rubes et al, 1998;Showell et al, 2013;Showell et al, 2014;Skalkidou et al, 2017;Van et al, 2017;Varshini et al, 2012) after reviewing the titles and abstracts. Full papers were obtained for the remaining 5 articles and reviewing were done thoroughly (Figure 1).…”
Section: Studies Selectedmentioning
confidence: 99%